Gender-Based Assessment in the Attitude Towards Social Values of the Pre-Service Teachers - Bazan, Wendy T.; Ledesma, Kate; Handang, Juspher; Quililan, Crizy Jane; Saldariega, Lyka (Journal of Learning on History and Social Sciences, 2024)
Social values have become the guide of a person where it judges the action whether the action that has been taken is acceptable or not. This study will explore the attitude towards social values of the Pre-Service Teachers and determine if there is a significant difference in the attitude towards social values among the respondents when data are grouped according to gender. A total of 89 collected responses where 50 of them are female and 39 of them are male were analyzed using the Statistical Package for the Social Sciences (SPSS) version 20. Pre-Service Teachers’ attitude towards social values in terms of their gender, results has shown that both genders reflect a result of somehow positive attitude towards social values with an average mean of 3.9164 and 4.0296 respectively. Moreover, both genders also reflect a somehow positive attitude with an average mean of 3.98. Overall, it is also revealed that gender does not affect the attitude towards social values of Pre-Service Teachers,in this sense, values education must be given importance in moulding the social values of the Pre-Service Teacher regardless of their gender whether they are male or female for the improvement of one’s social character as it will be beneficial in the cultivation of a harmonious school culture.